Why branded hotels can outperform non-branded competitors - Milburn, Robert (Henry Stewart Talks, 2009)
What is a brand?, Intangible value of brands, It is all about market share, Price, Brands can generate higher performance, Branded versus non-branded hotels, What is a brand worth?, Willingness to pay for brand, Brand owners spend more on advertising and PR, Branded hotel performance versus unbranded, Brands can deliver value, Does new technology advantage brands?